Economics : - McConnell, Campbell R. (McGraw-Hill/Irwin, 2002)
sample of the book's new discussions and analyzes include: the switch to GDP accounting; Soviet economy in transition; economics and the environment; the crisis in American financial institutions; economics of information; strategic behaviour; public choice and tax analysis ...